Analysis of the interaction between tunnel support and surrounding rock considering pre-reinforcement. (September 2021) - Sun, Zhenyu; Zhang, Dingli; Fang, Qian; Dui, Guansuo; Tai, Qimin; Sun, Fanwen
Highlights: Support-surrounding rock interaction considering pre-reinforcement are analyzed. Critical tunnel displacements defining seven transitions are presented. Fictitious support pressures for six configurations are solved. Proposed model excels the traditional CCM and the classical Carranza's model. Abstract: The behavior of support-surrounding rock interaction considering pre-reinforcement is investigated in this paper. Since previous analyses give little consideration to the influence of pre-reinforcement on the support-surrounding rock interaction, the equivalent material approach is adopted such that the ground strength is improved as the result of pre-reinforcement. The fictitious support pressure is introduced to quantify the spatial effect of excavation face, whose solution varies with the configurations of the surrounding rock based on the plastic zone distributions. The compatibility equations of tunnel displacement and support pressure are established accounting for the tunnel displacement prior to support installation. Using the critical displacements defining the transition of different configurations, an analytical method for the whole process of support and surrounding rock action is proposed. Plane-strain analysis is performed to obtain the tunnel displacement and reaction pressure of primary support along the tunnel axis. The proposed method allows a fast dimensioning of the primary support considering the effect of pre-reinforcement. The analytical results are validated by 3D numerical simulations and in-situ measurement. Additionally, a comparison reveals that the proposed model excels the traditional convergence-confinement method in solving the mentioned problem.